If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(j + 5) = 6 Reorder the terms: 8(5 + j) = 6 (5 * 8 + j * 8) = 6 (40 + 8j) = 6 Solving 40 + 8j = 6 Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '-40' to each side of the equation. 40 + -40 + 8j = 6 + -40 Combine like terms: 40 + -40 = 0 0 + 8j = 6 + -40 8j = 6 + -40 Combine like terms: 6 + -40 = -34 8j = -34 Divide each side by '8'. j = -4.25 Simplifying j = -4.25
| 1(x+2)=-3x | | 0+y=11 | | 6g-(g-7)=132 | | -9x-19=-199 | | 23x=60x | | 5(4-2k)-4K=90 | | 6xy-7xy+8x+3=-6y+6 | | 4.8-9.6x= | | 4.50+2.25n=31.50 | | y=3.1x-0.1 | | -5c+4=4 | | -x-3+x=2x-7 | | (1n-8)-(-2+2)= | | -2-6(6b+5)=-248 | | 30+0.25x=59.5 | | 7-4w= | | 3(2+y)-4v=v+16 | | 4(8p-3)= | | -3+15=-3t+5t | | 30.00+0.25x=59.5 | | 7x=4x+50 | | 20+3(2+5c)= | | 14x+8= | | y=1.7x-5.4 | | 5(6v-2)=-70 | | 3z+8=6z+7 | | -8+4x=6x+2x | | -9u-17=-2[u-2] | | -9(3n+6)=31 | | -2.8-(-9.3)= | | 25=7+13-4s | | (2-1k)-3(-4K+2)= |